(untitled) (Vietnam Journal of Community Medicine, 2022)
Objectives: Describe the use of drugs to treat type 2 diabetes by outpatients at Nam Dinh General Hospital in October 2021. Subjects and methods: A cross-sectional descriptive study on 1599 prescriptions of patients undergoing examination and treatment for type 2 diabetes. Results: The prevalence of the disease between men and women was 49.4/50, 6%, the age group most affected is from 61 to 79. The monotherapy regimen is quite commonly used, accounting for 58.7%, the drug treatment: insulin is used the most, accounting for 52.6%, Metformin and sulfonylurea is the most commonly used combination, accounting for 21.2%. Most of the pairs interact at a cautious level, monitoring and monitoring blood glucose levels to adjust the dose to suit the clinical response of the patient.